PERENCANAAN PROGRAM LITERACTION UNTUK MENINGKATKAN MINAT BACA DI PKBM SUKAMULYA KOTA BANDUNG DENGAN POTENSI KAMPUNG WISATA LITERASI KREATIF - Wibowo, Eka Avrilliany (Jendela PLS, 2025)
This research aims to plan a literacy program, "LITERACTION," to enhance reading interest at PKBM Sukamulya, Bandung City. Through interviews with local stakeholders, PKBM managers, and the community, this study identifies the needs, issues, and potential of the area. Sukamulya, as a Creative Literacy Tourism Village (KWK), has a middle to lower economy and faces challenges such as underutilization of KWK potential, low community participation, and a lack of collaboration between community organizations.With 74 personnel and 187 learners, PKBM Sukamulya has met 75% of community needs. There are potentials and issues such as waste problems, the impact of online business trends, and the underutilization of KWK potential. In addressing these issues, this study designs the LITERACTION program with a focus on three strategies: maximizing KWK, increasing community participation, and building collaboration between community organizations. The first strategy involves a SWOT analysis to leverage strengths, address weaknesses, capitalize on opportunities, and mitigate threats in optimizing KWK. The second strategy includes education and training to enhance community capacity, strengthen community institutions, and build partnerships with the government. The third strategy focuses on building collaboration with stages of problem setting, direction setting, and implementation. It is expected that the LITERACTION program can serve as a model for improving literacy at PKBM Sukamulya, bringing positive change, and creating a sustainable literacy culture. Keyword : Literacy, Creative Literacy Tourism Village, LITERACTION, SWOT, Community Participation, Community Organization Collaboration